Thermal performance of lithium-ion battery thermal management system by using mini-channel cooling - Qian, Zhen; Li, Yimin; Rao, Zhonghao (Energy conversion and management, 2016)
•Three-dimensional numerical models of lithium-ion battery are established.•The coolant distribution in the cold-plate is non-uniform.•The heat generation of the battery is changeable during the discharge. Thermal management is indispensable to lithium-ion battery pack especially within high power energy storage device and system. To investigate the thermal performance of lithium-ion battery pack, a type of liquid cooling method based on mini-channel cold-plate is used and the three-dimensional numerical model was established in this paper. The effects of number of channels, inlet mass flow rate, flow direction and width of channels on the thermal behaviors of the battery pack were analyzed. The results showed that the mini-channel cold-plate thermal management system provided good cooling efficiency in controlling the battery temperature at 5C discharge. A 5-channel cold-plate was enough and the temperature could be evidently reduced by increasing the inlet mass flow rate. Additionally, for the bad temperature uniformity in the design 1, design 2 was proposed and compared with the design 1. The maximum temperature and temperature difference decreased 13.3% and 43.3%, respectively. Temperature uniformity was significantly improved.